Mechanistic Elucidation of green seaweed compounds in orthodontic relapse management via RANKL/TNF-α-mediated ROS/Keap1/Nrf2 signaling: In silico and Ex Vivo studies - Ananto Ali Alhasyimi; Alexander Patera Nugraha; Aulia Ayub; Trianna Wahyu Utami; Timothy Sahala Gerardo; Nuril Farid Abshori; Mohammad Adib Khumaidi; Trina Ekawati Tallei; Nurpudji Astuti Taslim; Bonglee Kim; Raymond Rubianto Tjandrawinata; Apollinaire Tsopmo; et al. (Journal of Agriculture and Food Research)
Orthodontic relapse, the return to a pre-treatment position after orthodontic correction, is driven by the RANKL/TNF-α-mediated ROS/Keap1/Nrf2 signaling axis. This mechanism triggers aseptic inflammation and oxidative stress, influencing bone resorption and formation. Antioxidants can mitigate oxidative stress, potentially improving post-orthodontic outcomes. This study explores the efficacy of antioxidant compounds derived from green seaweed/algae in managing orthodontic relapse. Green seaweed/algae extracts were prepared via sonication, and bioactive compounds were identified using ultra-performance liquid chromatography-electrospray ionization-tandem mass spectrometry (UPLC-ESI-MS/MS) analysis. Compounds underwent bioactivity prediction, toxicity assessment, and drug-likeness evaluation, revealing significant therapeutic potential. Network pharmacology and molecular docking identified key proteins associated with orthodontic relapse, including IL-1β, STAT3, ESR1, MAPK1, JAK2, and HMOX1. Molecular docking simulations indicated favorable binding energies for green seaweed compounds, particularly the alkaloids adenosine (ΔG −6.9 to −7.3 kcal/mol) and lycopodine (ΔG −6.3 to −8.5 kcal/mol), against targeted proteins, matching or outperforming standard drugs such as s-ibuprofen (ΔG −6.7 kcal/mol). In vitro assays confirmed the antioxidant activity of these compounds, with EC50 dose of 52.2–54.2 μg/mL for ABTS radical scavenging capacities. Protein expression analysis in tibial-femoral bone marrow cells further demonstrated the potential of green seaweed/algae compounds to suppress osteoclastogenesis by modulating the RANKL/TNF-α-mediated ROS/Keap1/Nrf2 pathway. This research highlights the promise of green seaweed-derived antioxidants in reducing oxidative stress and managing orthodontic relapse, providing a foundation for future therapeutic developments.